The Imperative Need for Writing Skills and Competence in English for Vocational Learners: A Comprehensive Literature Review - Herawati, Susi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The focus of this research includes aspects of language, linguistics, and literature skills, as well as their impact on human resource management and public organizations. Through qualitative descriptive analysis methods, this study reveals that language skills, including grammar, vocabulary, and syntax, are the main foundation of writing competence. The results of this study show that linguistics and exposure to literature play an important role in developing writing excellence. Linguistic principles enrich students' understanding of sentence structure and coherence, while exposure to literature stimulates creativity and enriches writing styles. The integration of these components into the vocational curriculum is a practical strategy to strengthen overall writing skills. In addition, this study highlights the importance of writing competence in the context of human resource management. Students with strong writing skills are better equipped to make convincing job applications and communicate effectively in the context of human resource management. This demonstrates the need for vocational institutions to work with career services to provide the guidance and resources needed by students to succeed in HR-related communication. This research confirms that clear and effective written communication is very important in public organizations. Good writing skills ensure transparency, accountability, and accessibility of information within this organization.